Development of Instructional Materials for Electrochemical Module Class XII Science High School Students with Guided Inquiry Learning Approach - Lilik Fatmawati (Jurnal Pendidikan Sains, 2013)
Pengembangan Bahan Ajar Modul Elektrokimia untuk Siswa SMA Kelas XII IPA dengan Pendekatan Pembelajaran Inkuiri Terbimbing Abstract: The aim of this study was to determine the feasibility and effectiveness of the electrochemical module for high school students of class XII results of development. Electrochemical module of the development consists of two learning activities, ie to the material Volta cells and electrolysis cells for the material. Results of the assessment by two chemistry lecturer, State University of Malang and two chemistry teachers XII as an expert content / learning material for eligibility contents was 92.9%, for eligibility and completeness of presentation is 91.1%, and for the eligibility of language is 92.3% , which is classified as very feasible criteria. Overall the average value was 92.1 feasibility. Effectiveness module is indicated by the results of the development of perception and student learning outcomes. Students' perceptions obtained from student assessment results to module development. In the limited field trials obtained average value is 81.8 for all aspects of the maximum value of 100. Obtaining the average value of student learning outcomes for the cognitive aspect is 83.3, for the affective aspect is 82.3, and for the psychomotor aspect is 83.8 out of 100. The maximum value of the overall results of the study showed that the electrochemical module for high school students Class XII Science development results are very decent and very effectively used in the learning process. Key Words: guided inquiry, electrochemical module, model 4-D Abstrak: Tujuan penelitian ini adalah mengetahui kelayakan, dan keefektifan modul elektrokimia untuk siswa SMA kelas XII hasil pengembangan. Modul Elektrokimia hasil pengembangan terdiri dari dua kegiatan belajar, yaitu untuk materi sel Volta dan untuk materi sel elektrolisis. Hasil penilaian oleh dua dosen kimia Universitas Negeri Malang dan dua guru kimia kelas XII sebagai ahli isi/materi pem-belajaran untuk kelayakan isi adalah 92,9%, untuk kelayakan dan kelengkapan penyajian adalah 91,1%, dan untuk kelayakan kebahasaan adalah 92,3%, yang tergolong kriteria sangat layak. Secara keseluruhan rata-rata nilai kelayakan tersebut adalah 92,1. Efektifitas modul hasil pengembangan ditunjukkan oleh persepsi dan hasil belajar siswa. Persepsi siswa diperoleh dari penilaian siswa terhadap modul hasil pengembangan. Pada ujicoba lapangan terbatas diperoleh nilai rata-rata untuk seluruh aspek adalah 81,8 dari nilai maksimum 100. Perolehan rata-rata nilai hasil belajar siswa untuk aspek kognitif adalah 83,3, untuk aspek afektif adalah  82,3, dan untuk aspek psikomotorik adalah 83,8 dari nilai maksimum 100. Hasil keseluruhan penelitian menunjukkan bahwa Modul Elektrokimia untuk siswa SMA Kelas XII IPA hasil pengembangan sangat layak dan sangat efektif digunakan dalam proses pembelajaran.Kata kunci: inkuiri terbimbing, modul elektrokimia, model 4-D